Battery packaging adhesive film, application thereof and n-type Topcon photovoltaic module
By using ethylene/α-olefin copolymer and metallocene homopolymer with carbon-carbon double bonds at the end of the molecular chain in the photovoltaic adhesive film, the problems of additive migration and corrosion in n-type Topcon battery modules are solved, and good results are achieved The anti-PID performance and water-blocking effect ensure the long-term stability of the components.
Patent Information
- Application Number
- CN202411669615.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing photovoltaic films have additive migration and corrosion problems in n-type Topcon battery modules, which affect the power generation efficiency and long-term stability of the modules.
The battery encapsulation film is used to use ethylene/α-olefin copolymer as the matrix resin, and the metallocene homopolypropylene containing carbon-carbon double bonds at the end of the molecular chain is added as the functional resin, and the mass ratio of the main crosslinking agent and the functional resin is controlled. To improve the crosslinking degree and PID resistance of the adhesive film.
It effectively improves the additive migration problem in the adhesive film, improves the anti-PID performance and water-blocking effect, and ensures the long-term stability and power generation efficiency of n-type Topcon photovoltaic modules.
Smart Images

Figure BDA0005145471450000051 
Figure BDA0005145471450000052 
Figure BDA0005145471450000121
Abstract
Description
Technical Field
[0001] The present invention relates to the field of packaging materials for solar photovoltaic cell modules, in particular to the technical field of n-type Topcon cell packaging films, and further to a cell packaging film and an application thereof and an n-type Topcon photovoltaic module. Background Art
[0002] The utilization of solar energy requires the use of photovoltaic modules, which are mainly composed of five layers of photovoltaic glass, photovoltaic film, crystalline silicon cell, photovoltaic film, photovoltaic glass or backplane. The role of the photovoltaic film is to provide structural support and position the battery, as a physical isolation between the battery and other components, and to maintain electrical insulation between the battery and other components. Photovoltaic film mainly uses polyolefin materials. The current mainstream material is ethylene-vinyl acetate copolymer (EVA), but because it contains vinyl acetate groups, it will release acetic acid to corrode the battery during outdoor use. At the same time, it has low volume resistivity, high water vapor permeability, and poor PID resistance. Ethylene / α-olefin copolymer (POE, or described as ethylene-α-olefin copolymer) has excellent water resistance and better PID resistance, and is gradually replacing EVA as the main photovoltaic film application material. Since the current latest n-type TOPCon battery front coating is silver aluminum paste, water vapor intrusion corrodes the grid line silver paste in a high temperature and high humidity environment, resulting in blackening of the module and power attenuation. POE is more suitable for n-type Topcon batteries because of its excellent water resistance.
[0003] However, POE itself has poor compatibility with polar additives in the formula. During long-term storage or heating, the additives are prone to migration. At the same time, some polar by-products formed by residual additives during the lamination process will also migrate to the surface of the battery cell, causing corrosion to the battery cell, thereby affecting the power generation efficiency of the component.
[0004] The existing technology mainly involves adding some porous materials or cage compounds as precipitation prevention agents, or adding some adsorbents for adsorption.
[0005] CN111662655A discloses a POE photovoltaic adhesive film and a preparation method thereof. The POE photovoltaic adhesive film comprises: POE resin, antioxidant, cross-linking agent, coupling agent and anti-precipitation agent; the content of the anti-precipitation agent is 0.1-4%; the anti-precipitation agent is mainly some porous materials or cage compounds, which prevent the migration of liquid additives during storage or transportation, but the addition of porous materials or cage compounds will affect the light transmittance and other properties of the adhesive film.
[0006] CN118222197 A discloses a composite adhesive film for Topcon solar cells, characterized in that it comprises two acid-absorbing adhesive layers and a water-insulating layer sandwiched between the two acid-absorbing adhesive layers, wherein the acid-absorbing adhesive layers comprise silane derivatives and modified hydrotalcite, wherein the silane derivatives comprise one or two of modified silane and silane oligomers; and the water-insulating layer comprises ethylene-modified resin and compounded acrylate. However, the introduction of new additives still leads to the problem of additive migration. Summary of the invention
[0007] The present invention provides a battery encapsulation adhesive film and application thereof and an n-type Topcon photovoltaic module. The battery encapsulation adhesive film of the present invention is used in a photovoltaic module, especially an n-type Topcon photovoltaic module, which is beneficial to achieving both good water-blocking effect and anti-PID performance and improving the long-term stability of the module.
[0008] To achieve the purpose, the present invention provides the following technical solutions:
[0009] The present invention provides a battery packaging film, which is prepared by using raw materials including the following components in parts by weight:
[0010] 90-95 parts of ethylene / α-olefin copolymer,
[0011] 5-10 parts of functional resin,
[0012] Main cross-linking agent 0.2-2 parts;
[0013] Wherein, the functional resin is a metallocene homopolymer polypropylene containing a carbon-carbon double bond at the end of the molecular chain, and the mass ratio of the main cross-linking agent to the functional resin is 1:(5-10), preferably 1:(6-8).
[0014] The present invention also provides the use of the above-mentioned battery encapsulation film in a photovoltaic module, and preferably the photovoltaic module is an n-type Topcon photovoltaic module.
[0015] The present invention also provides an n-type Topcon photovoltaic module, comprising an upper photovoltaic glass, a first packaging film, an n-type Topcon battery cell, a second packaging film and a lower photovoltaic glass stacked in sequence; the first packaging film and / or the second packaging film is the battery packaging film described above.
[0016] The technical solution provided by the present invention has the following beneficial effects:
[0017] In the battery encapsulation film system using ethylene / α-olefin copolymer as the matrix resin, the present invention adopts metallocene homopolypropylene containing carbon-carbon double bonds at the molecular weight end as the functional resin, and the ethylene / α-olefin copolymer, the functional resin and the main cross-linking agent are combined and matched with each other according to the dosage range of the present invention, so as to improve the cross-linking degree of the film and improve the problem of auxiliary agent migration in the film. Moreover, the obtained encapsulation film can be used in the n-type Topcon photovoltaic module to take into account the comprehensive properties such as good anti-PID performance and water-blocking effect, thereby providing a guarantee for the long-term stability of the Topcon module. DETAILED DESCRIPTION
[0018] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.
[0020] The present invention provides a battery packaging film, which is prepared by using raw materials including the following components in parts by weight:
[0021] 90-100 parts of ethylene / α-olefin copolymer,
[0022] 5-10 parts of functional resin,
[0023] Main cross-linking agent 0.2-2 parts;
[0024] Wherein, the functional resin is a metallocene homopolymer polypropylene containing a carbon-carbon double bond at the end of the molecular chain, and the mass ratio of the main cross-linking agent to the functional resin is 1:(5-10).
[0025] In the present invention, in the battery encapsulation film system with ethylene / α-olefin copolymer as the matrix resin, a metallocene homopolymerized polypropylene containing a carbon-carbon double bond at the end of the molecular weight is used as a functional resin, and the ethylene / α-olefin copolymer, the functional resin and the main cross-linking agent are combined and matched with each other according to the above-mentioned dosage range, which can improve the cross-linking degree of the film, improve the problem of auxiliary agent migration in the film, and the obtained encapsulation film can be used in n-type Topcon photovoltaic modules. Good anti-PID performance and water barrier effect are taken into account, which provides a guarantee for the long-term stability of the Topcon module. In addition, the inventors have found that compared with other types of polypropylene, the functional resin using metallocene homopolymerized polypropylene is not easy to form crystal points in the process of preparing the encapsulation film. The obtained film is applied to the n-type Topcon photovoltaic module, which is not easy to cause damage to the battery cell structure, which is conducive to obtaining an n-type Topcon photovoltaic module with excellent performance.
[0026] In some examples, the amount of ethylene / α-olefin copolymer is 90, 93, 95, 97, 100 parts by mass, etc.; the amount of functional resin is 5, 7, 9, 10 parts by mass, etc.; the amount of main cross-linking agent is 0.2, 0.5, 0.7, 1.0, 1.5, 1.7, 2 parts by mass, etc.; the mass ratio of main cross-linking agent to functional resin is 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.
[0027] In a preferred embodiment, the mass ratio of the main cross-linking agent to the functional resin is 1:(6-8). Controlling the usage ratio of the two within a preferred range is beneficial to further improve the performance of the obtained battery encapsulation film.
[0028] Preferably, the functional resin is an organic powder made of metallocene homopolypropylene. Preferably, the melt index of the metallocene homopolypropylene is 10-30g / 10min, for example, 10g / 10min, 15g / 10min, 20g / 10min, 25g / 10min, 30g / 10min, etc., preferably 15-25g / 10min; the melting temperature is 140-160°C, for example, 140°C, 145°C, 150°C, 155°C, 160°C, etc., preferably 145-155°C. Metallocene homopolypropylene is a homopolypropylene produced using a metallocene catalyst. The metallocene homopolypropylene used in the present invention can use commercially available corresponding products, such as but not limited to MR2001, Metocene HM562S, etc. Preferably, the metallocene homopolymerized polypropylene is a powder with a particle size range of 10-100 μm, such as 10 μm, 30 μm, 50 μm, 70 μm, 90 μm, 100 μm, etc., preferably with a particle size range of 30-70 μm.
[0029] Due to the essential characteristics of metallocene catalysts, β-H elimination and β-CH 3 The chain transfer reaction terminates the growth of the molecular chain, thereby forming a double bond at the end of the molecular chain. The formation process is as follows:
[0030] (1) Schematic diagram of β-H elimination chain transfer reaction:
[0031]
[0032] (2) β-CH 3 Schematic diagram of chain transfer elimination reaction:
[0033]
[0034] In some embodiments, the ethylene / α-olefin copolymer is one or more of ethylene and butene copolymer, ethylene and hexene copolymer, and ethylene and octene copolymer. Preferably, the density of the ethylene / α-olefin copolymer is 0.85-0.88 g / cm 3 , for example 0.85, 0.86, 0.87, 0.88 g / cm 3 etc.; the melt index is 1-30g / 10min, for example, 1g / 10min, 5g / 10min, 10g / 10min, 15g / 10min, 20g / 10min, 25g / 10min, 30g / 10min, etc.
[0035] Further, the main cross-linking agent is selected from, but not limited to, one or more combinations of tert-butyl peroxide-2-ethylhexyl carbonate, tert-amyl peroxide-2-ethylhexyl carbonate, diisopropyl peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, and tert-butyl peroxy isopropyl carbonate; preferably tert-butyl peroxide-2-ethylhexyl carbonate.
[0036] Preferably, the raw material further comprises 0.2-1 parts by mass of a co-crosslinking agent, which is selected from, but not limited to, a combination of one or more of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate; triallyl isocyanurate is preferred.
[0037] Preferably, the raw materials further include 0.1-1 parts by mass of a silane coupling agent, and the specific amount used is, for example, 0.1, 0.3, 0.5, 0.7, 1 parts by mass, etc. The silane coupling agent is, for example, selected from, but not limited to, a combination of one or more of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyloxytrimethoxysilane, γ-methacryloxypropyloxytrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane; preferably, vinyltrimethoxysilane.
[0038] Preferably, the raw material further comprises 0.1-1 parts by mass of a light stabilizer, and the specific amount used is, for example, 0.1, 0.3, 0.5, 0.7, 1 parts by mass, etc. The light stabilizer is preferably a hindered amine light stabilizer, for example, selected from but not limited to a combination of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, mono(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;
[0039] Preferably, the raw material further comprises 0.1-1 parts by mass of an antioxidant, and the specific amount used is, for example, 0.1, 0.3, 0.5, 0.7, 1 parts by mass, etc. The antioxidant may be a commonly used type in the art, and there is no particular limitation on this; for example, the antioxidant is a composite antioxidant, such as β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester as a main antioxidant and tris(2,4-di-tert-butylphenyl) phosphite as a secondary antioxidant, and the mass ratio of the main antioxidant to the secondary antioxidant is, for example, but not limited to, 3:(1-3).
[0040] Furthermore, the battery encapsulation film provided by the present invention is preferably an encapsulation film for n-type Topcon batteries. The battery encapsulation film provided by the present invention is particularly suitable as an encapsulation film for n-type Topcon batteries and has good application performance.
[0041] The battery encapsulation film of the present invention can be prepared by using the existing preparation process in the art. As a preferred embodiment, the preparation steps of the battery encapsulation film specifically include:
[0042] S1, mixing the ethylene / α-olefin copolymer and the functional resin uniformly, and then extruding and granulating to obtain a polyolefin masterbatch;
[0043] S2, mixing the polyolefin masterbatch and other components uniformly, and performing cast extrusion molding after aging, for example, plasticizing, extruding, stretching, pulling, and winding in a casting machine to obtain a packaging film.
[0044] Preferably, in step S1, the extrusion granulation is carried out in a twin-screw extruder;
[0045] Preferably, in step S2, the aging is performed at 40-60° C., the aging time is, for example, 3-5 hours, and the aging is performed in an oven, for example;
[0046] Preferably, in step S2, the cast extrusion molding is carried out at 70-120°C, for example, in a cast machine.
[0047] The present invention also provides the use of the above-mentioned battery encapsulation film in a photovoltaic module, and preferably the photovoltaic module is an n-type Topcon photovoltaic module. The battery encapsulation film of the present invention is used in an n-type Topcon photovoltaic module to effectively reduce the residual additives in the film after lamination, effectively reduce the generation of by-products, thereby avoiding corrosion of the battery cell, and ultimately obtaining better anti-PID performance and water-blocking effect.
[0048] The present invention also provides an n-type Topcon photovoltaic module, comprising an upper photovoltaic glass, a first packaging film, an n-type Topcon cell, a second packaging film and a lower photovoltaic glass stacked in sequence; the first packaging film and / or the second packaging film is the cell packaging film described above. The above technical solution provided by the present invention has the following beneficial effects:
[0049] ① Based on the formulation system of ethylene / α-olefin copolymer as the base resin, metallocene homopolymer polypropylene containing carbon-carbon double bonds at the end of the molecular chain and the main cross-linking agent are used in accordance with the above-mentioned ratio range, and the main cross-linking agent and the functional resin are controlled to meet the above-mentioned ratio range, which can improve the precipitation problem of the auxiliary agent and is easy to process. The obtained encapsulation film is particularly suitable for use in n-type Topcon photovoltaic modules, and can take into account good water-blocking and anti-PID performance;
[0050] ② In the present invention, metallocene homopolymer polypropylene containing a carbon-carbon double bond at the end of the molecular chain is used as the functional resin. The double bond at the end of the molecular chain can participate in cross-linking, increase the cross-linking degree of the film, improve the migration of the additive, and enhance the overall water-blocking properties of the film, thereby preventing water vapor from invading and corroding the battery cell;
[0051] ③ When there is an excess of crosslinking agent in the film, the specific functional resin (metallocene polypropylene containing a carbon-carbon double bond at the end of the molecular chain) added by the present invention contains a large amount of side methyl groups, which can participate in the reaction to consume free radicals, thereby avoiding the occurrence of side reactions to produce some polar substances that lead to corrosion of the battery cell.
[0052] ④ The present invention controls the functional resin and the main cross-linking agent in the formula system within the above-mentioned ratio range, and uses them in a packaging film system based on ethylene / α-olefin copolymer as a matrix resin. The obtained packaging film has excellent anti-PID performance, which can greatly reduce the impact of additive residues on battery cells and ensure the long-term stability of the components.
[0053] Where specific experimental steps or conditions are not specified in the following examples, the experiments can be carried out according to the corresponding conventional experimental steps or conditions in the art. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.
[0054] Some of the raw materials in the following examples and comparative examples are described:
[0055] Ethylene-octene copolymer: DOW ENGAGE PV 8669, density 0.865 g / cm 3 , melt index is 14g / 10min;
[0056] Functional resin: Metallocene homopolymer polypropylene with carbon-carbon double bonds at the end of the molecular chain, brand name MR 2001, melt index 25g / 10min, melting temperature 151°C, particle size 40μm;
[0057] Example 1
[0058] This embodiment provides an n-type Topcon battery packaging film, and the preparation steps include:
[0059] Step S1: 95 parts by weight of ethylene-octene copolymer (DOW ENGAGE PV 8669) and 5 parts by weight of functional resin are uniformly mixed, and extruded and granulated by a twin-screw extruder to obtain polyolefin masterbatch A1;
[0060] Step S2: 100 parts by mass of polyolefin masterbatch A1, 1 part by mass of tert-butyl peroxide 2-ethylhexyl carbonate, 0.5 parts by mass of triallyl isocyanurate, 0.2 parts by mass of vinyl trimethoxysilane, 0.15 parts by mass of bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, and 0.1 parts by mass of composite antioxidant (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester: tris(2,4-di-tert-butylphenyl) phosphite=3:2, mass ratio) were mixed evenly, and placed in an oven at 45°C for aging and absorption for 4 hours to obtain formula B1;
[0061] Step S3: Put the completely absorbed and surface-dried formula material B1 into a casting machine with a head temperature of 90°C and a die head temperature of 100°C, and produce an n-type Topcon battery encapsulation film C1 with a thickness of 0.6 mm through plasticization, extrusion, stretching, pulling and winding.
[0062] Example 2
[0063] The process is carried out with reference to Example 1, except that: in step S1 of this example, 93 parts by mass of ethylene-octene copolymer (DOW ENGAGE PV 8669) and 7 parts by mass of functional resin are selected; the remaining steps are the same as those of Example 1, and an n-type Topcon battery encapsulation film C2 is obtained.
[0064] Example 3
[0065] The process is carried out with reference to Example 1, except that: in step S1 of this example, 90 parts by mass of ethylene-octene copolymer (DOW ENGAGE PV 8669) and 10 parts by mass of functional resin are selected; the remaining steps are the same as those of Example 1, and an n-type Topcon battery encapsulation film C3 is obtained.
[0066] Example 4
[0067] The process was carried out with reference to Example 1, except that: in step S1 of this embodiment, 93 parts by mass of ethylene-octene copolymer (DOW ENGAGE PV 8669) and 7 parts by mass of functional resin were selected; in step S2, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane was selected as the main cross-linking agent, and the remaining steps were the same as in Example 1, to obtain an n-type Topcon battery encapsulation film C4.
[0068] Example 5
[0069] The process was carried out with reference to Example 1, except that: in step S1 of this embodiment, 93 parts by mass of ethylene-octene copolymer (DOW ENGAGE PV 8669) and 7 parts by mass of functional resin were selected; in step S2, the main cross-linking agent was 0.8 parts by mass of tert-butyl peroxide 2-ethylhexyl carbonate, and the remaining steps were the same as in Example 1, to obtain an n-type Topcon battery encapsulation film C5.
[0070] Example 6
[0071] The process was carried out with reference to Example 1, except that: in step S1 of this embodiment, 93 parts by mass of ethylene-octene copolymer (DOW ENGAGE PV 8669) and 7 parts by mass of functional resin were selected; in step S2, the main cross-linking agent was 0.9 parts by mass of tert-butyl peroxide 2-ethylhexyl carbonate, and the remaining steps were the same as in Example 1, to obtain an n-type Topcon battery encapsulation film C6.
[0072] Example 7
[0073] The process was carried out with reference to Example 1, except that: in step S1 of this embodiment, 93 parts by mass of ethylene-octene copolymer (DOW ENGAGE PV 8669) and 7 parts by mass of functional resin were selected; in step S2, the main cross-linking agent was 1.1 parts by mass of tert-butyl peroxide 2-ethylhexyl carbonate, and the remaining steps were the same as in Example 1, to obtain an n-type Topcon battery encapsulation film C7.
[0074] Comparative Example 1 (without adding functional resin)
[0075] The process was carried out with reference to Example 1, except that: in step S1 of this comparative example, 100 parts by mass of ethylene-octene copolymer (DOW ENGAGE PV 8669) and 0 parts by mass of functional resin were selected; in step S2, the main cross-linking agent was 1 part by mass of tert-butyl peroxide 2-ethylhexyl carbonate, and the remaining steps were the same as in Example 1, to obtain an n-type Topcon battery encapsulation film D1.
[0076] Comparative Example 2
[0077] The process was carried out with reference to Example 1, except that: in step S1 of this comparative example, 80 parts by mass of ethylene-octene copolymer (DOW ENGAGE PV 8669) and 20 parts by mass of functional resin were selected; in step S2, the main cross-linking agent was 1 part by mass of tert-butyl peroxide 2-ethylhexyl carbonate, and the remaining steps were the same as in Example 1, to obtain an n-type Topcon battery encapsulation film D2.
[0078] Comparative Example 3 (Changing the Ratio of Main Cross-linking Agent and Functional Resin)
[0079] The process was carried out with reference to Example 1, except that: in step S1 of this comparative example, 95 parts by mass of ethylene-octene copolymer (DOW ENGAGE PV 8669) and 5 parts by mass of functional resin were selected; in step S2, the main cross-linking agent was 2 parts by mass of tert-butyl peroxide 2-ethylhexyl carbonate, and the remaining steps were the same as in Example 1, to obtain an n-type Topcon battery encapsulation film D3.
[0080] Comparative Example 4
[0081] The process is carried out with reference to Example 1, except that the functional resin used in step S1 of this embodiment is ordinary polypropylene Z30s (Zhenhai Refining and Chemical, melt index is 28g / 10min, melting point is 167°C, particle size is 40μm); the remaining steps are the same as in Example 1, and an n-type Topcon battery encapsulation film D4 is obtained.
[0082] The encapsulation films obtained by the above-mentioned embodiments and comparative examples were applied to the encapsulation of n-type Topcon photovoltaic modules and were evaluated by the following test methods. The evaluation results are listed in Table 1.
[0083] 1. Cross-linking degree test
[0084] The test method refers to the China Photovoltaic Industry Association standard T / CPIA 0006-2017 "Copolyolefin Film for Photovoltaic Module Encapsulation".
[0085] Sample preparation: overlap two films and cure them at 150°C for 18 minutes on a laminator. Then weigh 0.5g±0.01g and cut them into small particles with a size less than 3mm×3mm. Prepare 3 samples for each group.
[0086] After extraction with xylene at 140°C for 5 h, the mixture was placed in a vacuum oven at 140°C and dried to constant weight.
[0087] 2. Glass / encapsulation film peel strength
[0088] The test method refers to the national standard GB / T2790 "Adhesive 180° Peel Strength Test Method Flexible Materials to Rigid Materials".
[0089] Sample preparation: Take 2.1 mm thick ultra-white embossed tempered glass, the encapsulation film prepared in each embodiment or comparative example, and the n-type Topcon battery cell, and assemble them into a pre-pressed part in the order of tempered glass, encapsulation film, crystalline silicon battery cell, encapsulation film, and tempered glass. Put it into a vacuum laminator and cure it at 150°C for 18 minutes to prepare a peel strength test sample.
[0090] The test was carried out on a tensile testing machine with a tensile speed of 100 mm / min and a tensile stroke of 200 mm, and the peel strength value was recorded.
[0091] 3. Water vapor transmission rate test
[0092] The test method refers to the standard ASTM F1249 "Test method for water vapor transmission rate of plastic film and sheeting using a modulated infrared sensor".
[0093] Sample preparation: stack the release film / adhesive film / release film neatly and put them into a vacuum laminator. Laminate and cure at 150°C for 18 minutes. Take out the laminated adhesive film for testing.
[0094] The water vapor transmission rate (WVTR) was tested on a water vapor transmission rate meter under the conditions of 38° C. and 100% relative humidity.
[0095] 4. Yellowing index ΔYI
[0096] The test method refers to the standard ASTM E313-3010 "Procedure for Calculating the Whiteness and Yellowness Index of Color Coordinates Measured by Instruments".
[0097] Sample preparation: Take a certain area of packaging film, laminate it at 150℃ for 18 minutes, cut three rectangular samples of 30mm×50mm from the laminated film, and measure the yellowing index ΔYI on a colorimeter.
[0098] The yellowness index is measured before and after high temperature and high humidity aging (DH1000h, test conditions: 85°C, relative humidity 85%, 1000h), and the difference before and after high temperature and high humidity aging, i.e., the yellowing index ΔYI, is recorded.
[0099] 5. Appearance evaluation of encapsulated double-glass modules
[0100] Use encapsulation film to carry out double-glass module encapsulation test. Stack the tempered glass, encapsulation film, n-type Topcon cell, encapsulation film and tempered glass in this order to form a pre-pressed component. Put it into a vacuum laminator and cure it at 150°C for 18 minutes. Observe whether the double-glass module has bubbles or other appearance defects.
[0101] √: normal appearance; ▲: defects such as bubbles exist;
[0102] 6. High temperature and high humidity aging test
[0103] The damp heat aging test was carried out with reference to the national standard GB / T2423.3 "Basic environmental test procedures for electrical and electronic products Test Ca: Steady state damp heat test method".
[0104] Test conditions: 85°C, relative humidity 85%, 1000h.
[0105] The peel strength test method refers to the national standard GB / T2790 "Adhesive 180° Peel Strength Test Method Flexible Material to Rigid Material". The experimental results refer to the results of "DH1000h" corresponding to the peel strength in Table 1.
[0106] 7. Component power test
[0107] A photovoltaic module is prepared using the encapsulation film in the above-mentioned embodiment and the comparative example. The photovoltaic module consists of tempered glass, encapsulation film, n-type Topcon cell, encapsulation film, and tempered glass. The modules are laminated at 150°C for 18 minutes, and the prepared modules are tested for PID power change before and after aging (85°C, 85% RH, -1500V, 192h).
[0108] The performance comparison of the encapsulation films prepared in the embodiment and the comparative example is shown in Table 1.
[0109] Table 1 Comparison of performance of encapsulation films prepared in Example and Comparative Example
[0110]
[0111]
[0112] It can be seen from the performance data of the above embodiments and comparative examples that the n-type Topcon battery encapsulation film provided by the present invention has a high degree of crosslinking (above 81%), can effectively ensure that the component is not affected by the high temperature of the outdoor environment during use, effectively block the intrusion of water vapor, and has a low water vapor permeability; at the same time, it can take into account good initial peel strength (>220N / cm) and peel strength after aging (>140N / cm), and low yellowness index (ΔYI<3); when used in n-type Topcon battery components, it not only has a good initial appearance and resistance to moisture and heat aging, but also has good anti-PID performance, effectively reduces the power attenuation of the component, and ensures the long-term stability of the component, with a power attenuation of <2.0% after 192h.
[0113] In preferred embodiments 2, 4, 6-7, the main cross-linking agent and the functional resin adopt a preferred mass ratio of 1: (6-8), which can achieve better results, higher cross-linking degree (reaching more than 84%), and lower water vapor permeability; and can take into account better initial peel strength (> 235N / cm) and peel strength after aging (> 155N / cm), and is used in n-type Topcon battery components, and has better anti-PID performance.
[0114] In the comparative examples, it is difficult to achieve a good balance among high cross-linking degree, excellent water barrier performance, moisture and heat aging resistance and anti-PID performance.
[0115] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A battery packaging film, characterized in that: The raw materials comprising the following components are prepared: 90-95 parts of ethylene / α-olefin copolymer, 5-10 parts of functional resin, Main cross-linking agent 0.2-2 parts; Wherein, the functional resin is a metallocene homopolymer polypropylene containing a carbon-carbon double bond at the end of the molecular chain, and the mass ratio of the main cross-linking agent to the functional resin is 1:(5-10), preferably 1:(6-8).
2. The battery packaging film according to claim 1, characterized in that: The metallocene homopolymer polypropylene has a melt index of 10-30 g / 10 min and a melt temperature of 140-160° C. Preferably, the metallocene homopolymerized polypropylene is a powder with a particle size ranging from 10 to 100 μm.
3. The battery packaging film according to claim 1 or 2, characterized in that: The ethylene / α-olefin copolymer is one or more of ethylene and butene copolymer, ethylene and hexene copolymer, and ethylene and octene copolymer; And / or, the density of the ethylene / α-olefin copolymer is 0.85-0.88 g / cm 3 , the melt index is 1-30g / 10min.
4. The battery encapsulation film according to any one of claims 1 to 3, characterized in that: The main cross-linking agent is selected from one or more combinations of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, diisopropyl peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, and tert-butyl peroxy isopropyl carbonate; preferably tert-butyl peroxy-2-ethylhexyl carbonate.
5. The battery encapsulation film according to any one of claims 1 to 4, characterized in that: The raw materials further include 0.2-1 parts by mass of a co-crosslinking agent; preferably, the co-crosslinking agent is selected from a combination of one or more of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate; And / or, the raw materials further include 0.1-1 parts by mass of a silane coupling agent; preferably, the silane coupling agent is selected from a combination of one or more of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyloxytrimethoxysilane, γ-methacryloxypropyloxytrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane.
6. The battery packaging film according to any one of claims 1 to 5, characterized in that: The raw materials further include 0.1-1 parts by mass of a light stabilizer; preferably, the light stabilizer is a hindered amine light stabilizer, preferably selected from a combination of one or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, mono(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate; And / or, the raw material further comprises 0.1-1 parts by mass of an antioxidant.
7. The battery encapsulation film according to any one of claims 1 to 6, characterized in that: The battery packaging film is a packaging film for n-type Topcon batteries.
8. The battery encapsulation adhesive film according to any one of claims 1 to 7, characterized in that: The steps of preparing the battery encapsulation film include: S1, mixing the ethylene / α-olefin copolymer and the functional resin uniformly, and then extruding and granulating to obtain a polyolefin masterbatch; S2, mixing the polyolefin masterbatch and other components uniformly, and performing cast extrusion molding after aging; Preferably, in step S1, the extrusion granulation is carried out in a twin-screw extruder; Preferably, in step S2, the aging is carried out at 40-60° C., and the aging time is, for example, 3-5 hours; Preferably, in step S2, the cast extrusion molding is performed at 70-120°C.
9. Use of the battery encapsulation film according to any one of claims 1 to 8 in a photovoltaic module, wherein the photovoltaic module is preferably an n-type Topcon photovoltaic module.
10. An n-type Topcon photovoltaic module, comprising an upper photovoltaic glass, a first packaging film, an n-type Topcon cell, a second packaging film and a lower photovoltaic glass which are stacked in sequence; characterized in that: The first packaging film and / or the second packaging film is the battery packaging film according to any one of claims 1 to 8.
Citation Information
Patent Citations
POE photovoltaic adhesive film and preparation method thereof
CN111662655A
Composite adhesive film for Topcon solar cell as well as preparation method and application of composite adhesive film
CN118222197A
Novel photovoltaic encapsulation glue film, as well as preparation method and using method thereof
CN102766412A
Functionalized olefin polymers
US20040220320A1